The clinical and virological features of two children's coinfections with human adenovirus type 7 and human coronavirus-229E virus - Liu, Shelan; Zhu, An; Pan, Jinren; Ying, Lihong; Sun, Wanwan; Wu, Hanting; Zhu, Haiying; Lou, Haiyan; Wang, Lan; Qin, Shuwen; Yu, Zhao; Cai, Jian; et al. (Frontiers in Public Health, 2022)
Objective: Human adenovirus (HAdV) coinfection with other respiratory viruses is common, but adenovirus infection mixed with HCoV-229E is very rare. Study Design and Setting: Clinical manifestations, laboratory examinations, and disease severity were compared between the HAdV coinfected with HCoV-229E, mono-adenovirus, and mono-HCoV-229E groups. Results: Among 24 hospitalized children, two with HAdV-Ad7 coinfection with HCoV-229E and 21 with a single adenovirus infection were identified from July to August 2019. Additionally, three adult asymptotic cases with HCoV-229E were also screened. No significant difference in age was found in the coinfection and mono-adenovirus groups (11 years vs. 8 years, p = 0.332). Both groups had the same incubation (2.5 days vs. 3 days, p = 0.8302), fever durations (2.5 days vs. 2.9 days, p = 0.5062), and the hospital stays (7 days vs. 6.76 days, p = 0.640). No obvious differences were found in viral loads in the coinfection and single adenovirus group (25.4 vs. 23.7, p = 0.570), in the coinfection and single HCoV-229E group (32.9 vs. 30.06, p = 0.067). All cases were discharged completely. Conclusion: HAdV-Ad7 coinfected with HCoV-229E in healthy children may not increase the clinical severity and prolong the clinical course. The specific interaction mechanism between the viruses still needs further study.